Arctic Environmental Impact Assessment - Alaskan Workshop Summary Report - SDWG (2017)
Alaskan Workshop Summary; Alaskan Workshop Report: Meaningful Engagement of Indigenous Peoples within the Environmental Impact Assessment, Utqiaġvik/Barrow, Alaska, 27–29 November 2017